1966
DOI: 10.1098/rsta.1966.0025
|View full text |Cite
|
Sign up to set email alerts
|

On the praseodymium + oxygen system

Abstract: An isobaric survey of the system praseodymium oxide + oxygen has been made at oxygen pressures between 0 and 1 atm and in the temperature range 200 to 1150 °C. The derived isobaric sections enable a three-dimensional phase diagram (pressure, temperature, composition) to be constructed with considerable certainty and detail for the composition range PrOj.gg to PrOj.g*. Reasonable extensions to cover the complete range between the sesquioxide and dioxide are proposed, and a projection of the diagram on to the te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
47
1

Year Published

1998
1998
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 159 publications
(49 citation statements)
references
References 14 publications
1
47
1
Order By: Relevance
“…In this work, it was also shown that the temperatures necessary to obtain PrO 1.5 decrease with decreasing oxygen pressure. Therefore, the low values obtained in the present work can be explained since we used a base pressure of 1 · 10 −10 mbar compared to several 10 mbars used by Hyde et al [22].…”
mentioning
confidence: 87%
See 1 more Smart Citation
“…In this work, it was also shown that the temperatures necessary to obtain PrO 1.5 decrease with decreasing oxygen pressure. Therefore, the low values obtained in the present work can be explained since we used a base pressure of 1 · 10 −10 mbar compared to several 10 mbars used by Hyde et al [22].…”
mentioning
confidence: 87%
“…Whereas one species can be allocated to PrO [22]. In particular, during reduction additional oxidation states may be formed.…”
Section: Further Annealing At 150mentioning
confidence: 99%
“…Thus, the vertical lattice constant decreases to 3.09 Å. Since the bulk lattice constant of cubic praseodymia phases of different stoichiometry decreases as the oxygen content increases 25 (cf. the smaller lattice constant of PrO 2 compared to Pr 6 O 11 which can formally be conceived as mixture of PrO 2 and cubic Pr 2 O 3 where the latter has a 3.2% larger lattice constant than PrO 2 ) we conclude that the plasma-treated praseodymia film possesses more oxygen than the untreated film.…”
Section: X-ray Diffractionmentioning
confidence: 99%
“…The bixbyite structure of c-Pr 2 O 3 can be considered as fluorite structure with periodically arranged oxygen vacancies. 9 The anion sublattice of c-Pr 2 O 3 ͑111͒ films forms antiphase boundaries ͑APBs͒ on Si͑111͒ since the size of the surface unit cell of c-Pr 2 O 3 ͑111͒ is four times the size of Si͑111͒ surface unit cell. APBs are disadvantageous in the field of heteroepitaxy, as reported for other oxide films.…”
mentioning
confidence: 99%
“…9 Therefore we associate the phase with d ␦ with understoichiometric PrO 2−␦ . At high temperatures praseodymium can only completely be oxidized at high O 2 pressure so that bulk PrO 2 usually has oxygen vacancies.…”
mentioning
confidence: 99%